List of non‐EU viruses and viroids of Cydonia Mill., Fragaria L., Malus Mill., Prunus L., Pyrus L., Ribes L., Rubus L. and Vitis L - Bragard, Claude; Dehnen‐Schmutz, Katharina; Gonthier, Paolo; Jacques, Marie‐Agnès; Jaques Miret, Josep Anton; Justesen, Annemarie Fejer; MacLeod, Alan; Magnusson, Christer Sven; Milonas, Panagiotis; Navas‐Cortes, Juan A; Parnell, Stephen; Potting, Roel; et al. (EFSA journal, 2019)
The Panel on Plant Health performed a listing of non‐EU viruses and viroids (reported hereinafter as viruses) of Cydonia Mill., Fragaria L., Malus Mill., Prunus L., Pyrus L., Ribes L., Rubus L. and Vitis L. A systematic literature review identified 197 viruses infecting one or more of the host genera under consideration. Viruses were allocated into three categories (i) 86 non‐EU viruses, known to occur only outside the EU or having only limited presence in the EU (i.e. reported in only one or few Member States (MSs), known to have restricted distribution, outbreaks), (ii) 97 viruses excluded at this stage from further categorisation efforts because they have significant presence in the EU (i.e. only reported so far from the EU or known to occur or be widespread in some MSs or frequently reported in the EU), (iii) 14 viruses with undetermined standing for which available information did not readily allow to allocate to one or the other of the two above groups. Comments provided by MSs during consultation phases were integrated in the opinion. The main knowledge gaps and uncertainties of this listing concern (i) the geographic distribution and prevalence of the viruses analysed, in particular when they were recently described; (ii) the taxonomy and biological status of a number of poorly characterised viruses; (iii) the host status of particular plant genera in relation to some viruses. The viruses considered as non‐EU and those with undetermined standing will be categorised in the next steps to answer a specific mandate from the Commission to develop pest categorisations for non‐EU viruses. This list does not imply a prejudice on future needs for a pest categorisation for other viruses which are excluded from the current categorisation efforts. This publication is linked to the following EFSA Journal articles: http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2019.5590/full, http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2019.5669/full, http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2019.5735/full, http://onlinelibrary.wiley.com/doi/10.2903/j.efsa.2019.5766/full